2016
DOI: 10.3344/kjp.2016.29.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of a Symptomatic Discal Cyst by Percutaneous C-arm Guided Aspiration

Abstract: Although discal cysts are a rare cause of low back pain and radiculopathy. Currently, surgical excision is usually the first-line treatment for discal cysts. However, alternative treatment methods have been suggested, as in some cases symptoms have improved with interventional therapies. A 27-year-old man presented with an acute onset of severe pain, and was found to have a discal cyst after an open discectomy. The patient underwent cyst aspiration and steroid injection through the facet joint under C-arm guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Although discal cysts have been reported to occur in the intraspinal extraepidural area, 1,2,5 this is a rare case caused by the entry pathway of the PED on the intervertebral disc. The pathogenesis and etiology are still unclear.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although discal cysts have been reported to occur in the intraspinal extraepidural area, 1,2,5 this is a rare case caused by the entry pathway of the PED on the intervertebral disc. The pathogenesis and etiology are still unclear.…”
Section: Discussionmentioning
confidence: 92%
“…Although there are a few reports of lesions that resolved with conservative therapy, good outcomes and low recurrence rates have been obtained in most cases through aspiration and surgical treatment, such as microendoscopic discectomy and PED. 5,10,11 Although it is possible that PED will not be able to completely resect the cyst, symptoms may be alleviated by decompression of the cyst contents and the intervertebral disc. Furthermore, the potential for recurrence can be reduced by annuloplasty using radiofrequency coagulation.…”
Section: Discussionmentioning
confidence: 99%
“…We summarized previous literature on discal cyst treatment and compiled the data (Table 4). 14,7,10,11,17,19–48) For patients with tolerable pain or without neurologic deficits, the literature suggests conservative treatment for discal cysts, initially. 4,6,45) Conservative management options include bed rest, analgesics, physical therapy, percutaneous steroid injection, and image-guided cyst aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…18 , 19 A study reported that they are accessible to each other. 24 Therefore, we should pay close attention to FJI like other treatments.…”
Section: Discussionmentioning
confidence: 99%